ПОДОЛАННЯ ІНФОРМАЦІЙНОЇ АСИМЕТРІЇ, ПОВНОТА ТА ОПЕРАТИВНІСТЬ ПОДАННЯ ПОДАТКОВОЇ ЗВІТНОСТІ ЯК ПРЕВЕНТИВНІ ЗАХОДИ УХИЛЕННЯ ВІД ОПОДАТКУВАННЯ (International Journal of Innovative Technologies in Economy, 2018)
An asymmetry of information exists in any field of the economy. It negatively affects partnership between counterparties and on implementation of the state functions. The tax authorities and taxpayers are interested in minimizing the asymmetry of information and in tax reporting being complete and formulated in time. To achieve these goals, to avoid tax evasion and to increase the effectiveness of the financial and economic activity and state taxation policy, it is expedient to use innovative technologies in tax accounting and IT-platforms for cooperation between government bodies and entities. The solution of antagonistic needs of the counterparties of taxation is based on improvement of tax conditions and on a constant process of improving the effectiveness of information policy of both sides based on a partnership principles.